Chitosan-loaded MIL-68 (Al) composite sponge material as well as preparation method and application thereof
By loading MIL-68 (Al) in chitosan sponge, the chitosan/MIL-68 (Al) composite sponge material is prepared, which solves the problem of difficult separation and recovery of MOFs materials and high cost, and achieves efficient adsorption and removal of organic dyes in water, expanding the application range of adsorbents.
Patent Information
- Application Number
- CN202510276955.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-07-04
AI Technical Summary
Existing MOFs materials are not easy to separate and recover when adsorbed by water, and are costly, making it difficult to effectively remove complex organic pollutants such as methyl orange in water. Traditional adsorbent materials have limited removal effects on methyl orange and are complex in regeneration process.
By uniformly loading MIL-68 (Al) in chitosan sponge, using the viscosity of chitosan and metal organic frame structure to support the sponge structure, chitosan/MIL-68 (Al) composite sponge material is prepared to increase the specific surface area and adsorption sites and improve mechanical properties.
It has achieved low-cost, green and environmentally friendly and efficient removal of organic dyes in water, especially methyl orange, methylene blue and rhodamine, which significantly improves the adsorption and removal ability of organic dyes.
Smart Images

Figure CN120242978A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of environmental science and engineering, and particularly relates to a chitosan-loaded MIL-68(Al) composite sponge material, a preparation method thereof, and an application thereof. Background Art
[0002] In recent years, due to the continuous exploration and innovation in the field of materials science driven by the development of science and technology, and the strive to meet the diverse needs of multiple fields, the demand for high-performance materials in key application directions such as adsorption, separation, and catalysis is particularly urgent. Traditional adsorption materials such as activated carbon have adsorption properties, but they have obvious defects. In terms of adsorption selectivity, it is difficult for it to accurately remove complex organic pollutants and heavy metal ions in sewage, and the regeneration process is complex after adsorption saturation. Methyl orange is a commonly used azo dye in textile printing and dyeing, and its wastewater discharge is large. It is toxic. After entering the water body, it will reduce the transparency, hinder the photosynthesis of aquatic organisms, destroy the aquatic ecological balance, and its degradation products may also accumulate along the food chain, threatening human health, such as causing allergies, irritating the respiratory tract, and even having a carcinogenic risk.
[0003] Metal-organic framework (MOFs) materials are representatives of emerging porous materials. With their ultra-high specific surface area and adjustable pore structure, they have great potential in the fields of adsorption and catalysis. Among them, MIL-68(Al) performs outstandingly in gas adsorption, water body adsorption, and organic small molecule separation. However, most MOFs materials are in powder form, with disadvantages such as easy agglomeration, difficult shaping, poor mechanical stability, and difficult separation and recovery.
[0004] In order to solve the problem that MOFs materials are difficult to separate and recover when used for water body adsorption, Chinese Patent CN110102267B discloses an aluminum-based MOFs / chitosan composite microsphere, a preparation method thereof, and an application thereof. This invention uses the aluminum-based MOFs material MIL-68(Al) as the parent body, and obtains a composite microsphere with chitosan-coated surface under the co-crosslinking action of sodium alginate and chitosan. The particle size of the microsphere is about 2 mm, which is easy to separate and recover from water. And the aluminum-based MOFs / chitosan composite microsphere of this invention can achieve a removal efficiency equivalent to that of powder MOFs, and can efficiently adsorb and remove bisphenol A in water and quickly separate and recover the adsorption material from the water body. However, this adsorption material is used to adsorb and remove bisphenol A in the water body, and the removal effect on printing and dyeing pollutants such as methyl orange is unknown. Moreover, this invention can only solve the problem that MOFs materials are difficult to separate and recover when used for water body adsorption, and the adsorption effect of the obtained composite microsphere is limited, and its adsorption removal rate is only equivalent to that of the monomer aluminum-based MOFs material MIL-68(Al); furthermore, this adsorption material uses MOFs materials as the main material, which contains a large amount of MOFs materials, has a high cost, and requires a large amount of organic solvents such as N,N-dimethylformamide, causing environmental pollution.
[0005] Therefore, it is of great significance to provide a material with low cost, environmental friendliness and excellent adsorption and removal ability for organic dyes such as methyl orange. Summary of the Invention
[0006] Aiming at the deficiencies of the above prior art, one of the purposes of the present invention is to provide a preparation method of a chitosan-loaded MIL-68(Al) composite sponge material. The prepared composite sponge material can effectively remove organic dyes in aqueous solution, taking into account the environmental friendliness of the adsorption material while exerting a good adsorption effect.
[0007] The above object of the present invention is achieved by the following technical solutions:
[0008] A preparation method of a chitosan-loaded MIL-68(Al) composite sponge material, comprising the following steps: adding MIL-68(Al), chitosan powder, gelatin and glacial acetic acid into water, mixing evenly, adding a crosslinking agent, mixing evenly again, and obtaining the chitosan-loaded MIL-68(Al) composite sponge material after freeze-drying.
[0009] The main body of the chitosan / MIL-68(Al) composite sponge material prepared by the present invention is chitosan, and MIL-68(Al) is evenly distributed in the chitosan sponge. The sponge structure is supported by the metal-organic framework structure, and at the same time, the viscosity of chitosan is used to solve the forming problem of MIL-68(Al), endowing the material with better mechanical properties and obtaining a sponge-like material with excellent mechanical properties. In the chitosan / MIL-68(Al) composite sponge material of the present invention, MIL-68(Al) can not only act as an adsorbent to carry out synergistic adsorption with chitosan, but more importantly, it can support the sponge structure, forming a denser, larger specific surface area and more adsorption sites adsorption material, and capturing pollutant molecules by means of the large pore structure of the sponge, significantly improving the adsorption efficiency of the composite sponge material for organic dyes, and obtaining a composite sponge material with excellent adsorption and removal ability for organic pollutants in water.
[0010] Gelatin molecules contain various functional groups such as amino and carboxyl groups, which can interact with the hydroxyl and amino groups of chitosan, provide more sites for the crosslinking of chitosan, make the formed crosslinking network more stable, and improve the mechanical properties of the material.
[0011] Preferably, the mass ratio of MIL-68(Al), chitosan powder and gelatin is 1:(1-20):(0.2-0.8). More preferably, the mass ratio of MIL-68(Al), chitosan powder and gelatin is 1:(5-15):(0.2-0.8).
[0012] Preferably, the mass ratio of MIL-68(Al) to glacial acetic acid is 1:(6-10).
[0013] Preferably, the crosslinking agent is glutaraldehyde. More preferably, the crosslinking agent is a glutaraldehyde solution with a mass fraction of 2% - 10%, and the mass ratio of MIL-68(Al) to the glutaraldehyde solution is 1:(10 - 30).
[0014] Preferably, the time for freeze-drying is 24 - 72 h.
[0015] Preferably, the preparation method of MIL-68(Al) includes the following steps: adding soluble aluminum salt and terephthalic acid into N,N-dimethylformamide, stirring and dissolving to obtain a mixed solution, then carrying out hydrothermal reaction at 110 - 140 °C, collecting the solid product, and obtaining the MIL-68(Al) after washing and vacuum drying.
[0016] Preferably, the mass ratio of the soluble aluminum salt to terephthalic acid is 1:(0.8 - 1.2).
[0017] Preferably, the soluble aluminum salt is aluminum chloride and / or aluminum nitrate.
[0018] Preferably, the time for the hydrothermal reaction is 15 - 20 h.
[0019] Preferably, in the preparation method of MIL-68(Al), the temperature for vacuum drying is 50 - 80 °C, and the time is 10 - 14 h.
[0020] Another object of the present invention is to provide a chitosan-loaded MIL-68(Al) composite sponge material prepared by the above preparation method.
[0021] Preferably, the chitosan-loaded MIL-68(Al) composite sponge material uses a chitosan sponge as a carrier, and the MIL-68(Al) is uniformly distributed in the chitosan sponge.
[0022] Another object of the present invention is to provide the application of the chitosan-loaded MIL-68(Al) composite sponge material prepared by the above preparation method in adsorbing and removing methyl orange, methylene blue or rhodamine in water bodies.
[0023] Compared with the prior art, the advantages of the present invention are as follows:
[0024] (1) The main body of the chitosan / MIL-68(Al) composite sponge material prepared by the present invention is chitosan, and MIL-68(Al) is uniformly distributed in the chitosan sponge to play a role in supporting the structure. Even with a small amount of MIL-68(Al), it can effectively improve the adsorption effect of the material on pollutants. With a low content of MIL-68(Al), while maintaining a high level of dye removal effect, it also takes into account the cost and green environmental protection of the adsorption material.
[0025] (2) Compared with chitosan and MIL-68(Al), loading MIL-68(Al) onto chitosan in the present invention can significantly increase the specific surface area of the material, increase the adsorption sites for dye pollutants, and at the same time, a sponge structure can be supported by the metal-organic framework structure. The obtained chitosan / MIL-68(Al) composite sponge material has a large specific surface area and many adsorption sites, and the removal ability of organic dyes is significantly improved, and it can effectively remove organic dyes in aqueous solution.
[0026] (3) The chitosan / MIL-68(Al) composite sponge material of the present invention not only has a good adsorption effect on methyl orange dye, but also has a good adsorption and removal ability for organic dyes such as methylene blue and rhodamine, greatly expanding the application range of the adsorbent. Brief Description of the Drawings
[0027] Figure 1 XRD patterns of the chitosan / MIL-68(Al) composite sponge materials prepared in Examples 1 to 3, the MIL-68(Al) material prepared in Comparative Example 1, and the chitosan sponge material prepared in Comparative Example 2;
[0028] Figure 2 SEM spectrum of the MIL-68(Al) material prepared in Comparative Example 1;
[0029] Figure 3 SEM spectrum of the chitosan sponge material prepared in Comparative Example 2;
[0030] Figure 4 SEM spectrum of the chitosan / MIL-68(Al) composite sponge material prepared in Example 2. Detailed Embodiments
[0031] The technical solutions of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the scope of protection of the present invention.
[0032] The embodiments of the present invention provide a preparation method of a chitosan-supported MIL-68(Al) composite sponge material, including the following steps: adding MIL-68(Al), chitosan powder, gelatin and glacial acetic acid into water, mixing evenly, adding a cross-linking agent, mixing evenly again, and obtaining the chitosan-supported MIL-68(Al) composite sponge material after freeze-drying.
[0033] In some embodiments, the mass ratio of the MIL-68(Al), chitosan powder, and gelatin is 1:(1 - 20):(0.2 - 0.8). For example, the mass ratio of the MIL-68(Al), chitosan powder, and gelatin can be 1:1:0.5, 1:1:0.2, 1:1:0.8, 1:5:0.5, 1:10:0.5, 1:15:0.5, 1:20:0.5, etc.
[0034] In some embodiments, the mass ratio of the MIL-68(Al) and glacial acetic acid is 1:(6 - 10). For example, the mass ratio of the MIL-68(Al) and glacial acetic acid can be 1:6, 1:7, 1:8, 1:9, 1:10, etc.
[0035] In some embodiments, the crosslinking agent is a glutaraldehyde solution with a mass fraction of 2% - 10%, and the mass ratio of the MIL-68(Al) and the glutaraldehyde solution is 1:(10 - 30).
[0036] In some embodiments, the time for freeze-drying is 24 - 72 h. For example, the time for freeze-drying can be 24 h, 36 h, 48 h, 72 h, etc.
[0037] In step S1, the MIL-68(Al) can be directly used as a commercially available product or can be prepared by oneself. When using the self-prepared MIL-68(Al), the preparation method of the MIL-68(Al) includes the following steps: adding a soluble aluminum salt and terephthalic acid to N,N-dimethylformamide, stirring and dissolving to obtain a mixed solution, then carrying out a hydrothermal reaction at 110 - 140 °C, collecting the solid product, and obtaining the MIL-68(Al) after washing and drying.
[0038] The soluble aluminum salt is aluminum chloride and / or aluminum nitrate; the mass ratio of the soluble aluminum salt and terephthalic acid is 1:(0.8 - 1.2).
[0039] Example 1
[0040] This example provides a preparation method of a chitosan-loaded MIL-68(Al) composite sponge material, including the following steps:
[0041] (1) Preparation of the MIL-68(Al) material
[0042] Add 0.35 g of aluminum chloride hexahydrate and 0.33 g of terephthalic acid to 10 mL of N,N-dimethylformamide, and stir well at room temperature until completely dissolved. Transfer the dissolved mixture to a polytetrafluoroethylene-lined autoclave and react at 130 °C for 18 h. After cooling to room temperature, collect the resulting solid by centrifugation, and then wash it three times with N,N-dimethylformamide and methanol in turn. Finally, dry the product under vacuum at 60 °C for 12 h to obtain the MIL-68(Al) material.
[0043] (2) Preparation of chitosan / MIL-68(Al) composite sponge material
[0044] Add 0.1 g of MIL-68(Al) material to a beaker containing 100 mL of ultrapure water. Then, add 0.1 g of chitosan powder, 0.05 g of gelatin, and 0.8 g of glacial acetic acid to the beaker in turn, and stir until a uniform and stable solution is formed. Add 1 g of a 5% glutaraldehyde solution to the above uniform solution for cross-linking, and stir again until a uniform solution is formed. After freeze-drying for 48 h, the chitosan / MIL-68(Al) composite sponge material is obtained.
[0045] Example 2
[0046] The preparation method of this example is basically the same as that of Example 1, except that in step (2), the mass of the chitosan powder is 1 g. That is, the mass ratio of the MIL-68(Al) material to the chitosan powder is 1:10.
[0047] Example 3
[0048] The preparation method of this example is basically the same as that of Example 1, except that in step (2), the mass of the chitosan powder is 2 g. That is, the mass ratio of the MIL-68(Al) material to the chitosan powder is 1:20.
[0049] Example 4
[0050] This example provides a preparation method of a chitosan-loaded MIL-68(Al) composite sponge material, including the following steps:
[0051] (1) Preparation of MIL-68(Al) material
[0052] 0.35 g of aluminum chloride hexahydrate and 0.42 g of terephthalic acid were added to 10 mL of N,N-dimethylformamide, and stirred well at room temperature until completely dissolved. The dissolved mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 115 °C for 20 h. After cooling to room temperature, the obtained solid was collected by centrifugation, and then washed three times with N,N-dimethylformamide and methanol successively. Finally, the product was vacuum dried at 50 °C for 14 h to obtain the MIL-68(Al) material.
[0053] (2) Preparation of chitosan / MIL-68(Al) composite sponge material
[0054] 0.1 g of MIL-68(Al) material was added to a beaker containing 100 mL of ultrapure water. Then, 0.1 g of chitosan powder, 0.02 g of gelatin, and 0.6 g of glacial acetic acid were added to the beaker in sequence and stirred until a uniform and stable solution was formed. 2.5 g of a 2% glutaraldehyde solution was added to the above uniform solution for crosslinking, and stirred again until a uniform solution was formed. After freeze-drying for 48 h, the chitosan / MIL-68(Al) composite sponge material was obtained.
[0055] Comparative Example 1
[0056] Preparation of MIL-68(Al) material
[0057] 0.35 g of aluminum chloride hexahydrate and 0.33 g of terephthalic acid were added to 10 mL of N,N-dimethylformamide, and stirred well at room temperature until completely dissolved. The dissolved mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 130 °C for 18 h. After cooling to room temperature, the obtained solid was collected by centrifugation, and then washed three times with N,N-dimethylformamide and methanol successively. Finally, the product was vacuum dried at 60 °C for 12 h to obtain the MIL-68(Al) material.
[0058] Comparative Example 2
[0059] Preparation of chitosan sponge material
[0060] 1 g of chitosan powder, 0.05 g of gelatin, and 0.8 g of glacial acetic acid were added to a beaker containing 100 mL of ultrapure water in sequence and stirred until a uniform and stable solution was formed. 1 g of a 5% glutaraldehyde solution was added to the above uniform solution for crosslinking, and stirred again until a uniform solution was formed. After freeze-drying for 48 h, the chitosan sponge material was obtained.
[0061] Figure 1XRD patterns of the chitosan / MIL-68(Al) composite sponge materials prepared in Examples 1 to 3, the MIL-68(Al) material prepared in Comparative Example 1, and the chitosan sponge material prepared in Comparative Example 2. From Figure 1 it can be seen that the chitosan / MIL-68(Al) composite sponge materials prepared in Examples 1 and 2 are basically the same as the MIL-68(Al) material prepared in Comparative Example 1 and the chitosan sponge material prepared in Comparative Example 2. The main peaks appear at 10°, 18°, and 28°. This indicates that the chitosan / MIL-68(Al) materials prepared in Examples 1 and 2 retain the crystal configuration of MIL-68(Al) while using chitosan as the carrier, and the crystal form is good. In Example 3, the diffraction peak intensity representing MIL-68(Al) decreases significantly because the proportion of added MIL-68(Al) decreases, resulting in a relatively low proportion in the chitosan / MIL-68(Al) composite sponge material.
[0062] Figure 2 SEM spectrum of the MIL-68(Al) material prepared in Comparative Example 1. It can be seen from the figure that the surface of the MIL-68(Al) material prepared in Comparative Example 1 is rough and uneven, and particle agglomeration occurs in some parts. Figure 3 SEM spectrum of the chitosan sponge material prepared in Comparative Example 2. It can be seen from the figure that there are many smooth folds on the surface of the chitosan sponge material, which significantly increases its specific surface area. Figure 4 SEM spectrum of the chitosan / MIL-68(Al) composite sponge material prepared in Example 2. It can be seen from the figure that the carrier chitosan sponge of the chitosan / MIL-68(Al) material of the present invention is Figure 3 similar, and both have obvious fold-like shapes on the surface, which significantly increases the specific surface area. At the same time, it can be clearly seen that a layer of MIL-68(Al) material is uniformly loaded on the surface of the chitosan / MIL-68(Al) material. The sponge structure is supported by the organic framework structure, endowing the material with better mechanical properties. After loading, it will also increase the specific surface area of the material to a certain extent and increase the adsorption sites for dye pollutants on the material.
[0063] Application Example 1
[0064] The materials prepared in each example and comparative example were used as adsorbents for the removal of methyl orange dye in water
[0065] 10 mg of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were taken and added to 20 mL of methyl orange solution with a concentration of 20 mg / L. The adsorption and degradation were carried out at room temperature for 10 min. After centrifugation, the supernatant was taken, and the change in the concentration of the methyl orange solution during the adsorption process was tested and analyzed by an ultraviolet spectrophotometer. The degradation rate results are shown in Table 1.
[0066] Table 1 Adsorption effect of chitosan / MIL-68(Al) composite sponge material on methyl orange
[0067]
[0068] As can be seen from the results in Table 1, the ability of the MIL-68(Al) material alone to remove the dye methyl orange is very limited. After a ten-minute degradation experiment, the degradation rate is only 14%. The chitosan sponge prepared in Comparative Example 2 has a higher ability to remove the dye methyl orange than the MIL-68(Al) material, but the overall removal ability is limited, and the degradation rate only reaches 48% after a ten-minute degradation experiment. By comparing Examples 1-3 and Comparative Examples 1-2, it can be seen that compared with the single MIL-68(Al) material or chitosan sponge material, the chitosan / MIL-68(Al) composite sponge material obtained by loading MIL-68(Al) onto chitosan in the present invention has a significantly improved ability to remove methyl orange. The degradation rate can reach over 80% after a ten-minute adsorption test, and the highest can reach up to 95%.
[0069] By comparing Examples 1-3, it can be seen that the final adsorption effect of the composite sponge material is affected by the content of MIL-68(Al) loaded in the material. In Example 3, due to the relatively low content of MIL-68(Al) loaded, the degradation efficiency is relatively low among the three. In Example 1, the content of MIL-68(Al) is the highest, but the degradation rate is slightly lower than that in Example 2. It may be that the excessive content of MIL-68(Al) in the material leads to agglomeration in the sponge material, which instead limits the performance of the material to a certain extent. Example 2 has the best degradation effect on methyl orange dye. After a ten-minute degradation experiment, the degradation rate can reach over 95%.
[0070] Application Example 2
[0071] The material prepared in the best Example 2 was used as an adsorbent for the removal of the dye methylene blue in water
[0072] 10 mg of the material prepared in Example 2 was taken and added to 20 mL of methylene blue solution with a concentration of 20 mg / L. Adsorption and degradation were carried out at room temperature for 6 h, and the degradation rate reached 95%.
[0073] Application Example 3
[0074] The material prepared in the best Example 2 was used as an adsorbent for the removal of the dye rhodamine in water
[0075] 10 mg of the material prepared in Example 2 was taken and added to 20 mL of rhodamine solution with a concentration of 20 mg / L. Adsorption and degradation were carried out at room temperature for 12 h, and the degradation rate reached 98%.
[0076] Although embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation method of a chitosan-loaded MIL-68(Al) composite sponge material, characterized in that, It includes the following steps: Add MIL-68(Al), chitosan powder, gelatin and glacial acetic acid into water. After mixing evenly, add a cross-linking agent and mix evenly again. After freeze-drying, a chitosan-loaded MIL-68(Al) composite sponge material is obtained.
2. The preparation method of a chitosan-loaded MIL-68(Al) composite sponge material according to claim 1, characterized in that, The mass ratio of the MIL-68(Al), chitosan powder and gelatin is 1:(1~20):(0.2~0.8).
3. The preparation method of a chitosan-loaded MIL-68(Al) composite sponge material according to claim 2, characterized in that, The mass ratio of the MIL-68(Al), chitosan powder and gelatin is 1:(5~15):(0.2~0.8).
4. The preparation method of a chitosan-loaded MIL-68(Al) composite sponge material according to claim 1, wherein, The mass ratio of the MIL-68(Al) to glacial acetic acid is 1:(6~10).
5. The preparation method of a chitosan-loaded MIL-68(Al) composite sponge material according to claim 1, characterized in that, The cross-linking agent is glutaraldehyde.
6. The preparation method of a chitosan-loaded MIL-68(Al) composite sponge material according to claim 1, characterized in that, The time of the freeze-drying is 24~72h.
7. The preparation method of a chitosan-loaded MIL-68(Al) composite sponge material according to claim 1, characterized in that, The preparation method of the MIL-68(Al) includes the following steps: Add a soluble aluminum salt and terephthalic acid into N,N-dimethylformamide. After stirring and dissolving, a mixed solution is obtained. Then, carry out a hydrothermal reaction at 110~140°C, collect the solid product, and obtain the MIL-68(Al) after washing and drying.
8. The preparation method of a chitosan-loaded MIL-68(Al) composite sponge material according to claim 7, characterized in that, The mass ratio of the soluble aluminum salt to terephthalic acid is 1:(0.8~1.2).
9. The chitosan-loaded MIL-68(Al) composite sponge material prepared by the preparation method according to any one of claims 1 to 8, characterized in that, The chitosan-loaded MIL-68(Al) composite sponge material uses a chitosan sponge as a carrier, and the MIL-68(Al) is evenly distributed in the chitosan sponge.
10. Application of the chitosan-loaded MIL-68(Al) composite sponge material prepared by the preparation method according to any one of claims 1~8 in adsorbing and removing methyl orange, methylene blue or rhodamine in water.
Citation Information
Patent Citations
An aluminum-based MOFs / chitosan composite microsphere, its preparation method and application
CN110102267B